الوعي الصحي لامراض السرطان لطلبة المعهد الطبي التقني (Journal of the College of Basic Education, 2025)
Current Research Objective:The aim of the current research is to identify the level of health awareness regarding cancer diseases among second-year students at the Institute of Technical Medicine / BaghdadTo achieve the research objective, the following questions were formulated:What is the level of health awareness among second-year students at the Institute of Technical Medicine / Bab Al-Muadham, Middle Technical University?Are there differences in the level of health awareness based on gender (male and female) among second-year students at the Institute of Technical Medicine / Bab Al-Muadham, Middle Technical University?Methodology:A tool was designed to measure health awareness of cancer diseases, consisting of 20 items covering four domains of health awareness. The tool was reviewed by a panel of experts in teaching methods and the health field to ensure its validity. To verify its reliability, it was administered to a pilot sample consisting of 20 students. After confirming its validity and reliability, the tool was applied to the research sample, which consisted of 194 second-year students from all departments of the InstituteResulta:To answer the first research question, the arithmetic mean for the research sample (194 students) was calculated. The results showed that the mean score was (70.08) with a standard deviation of (43.319). In comparison, the hypothetical mean of the tool was (40), indicating that there is a statistically significant difference. This suggests that the second-year students possess a good level of health awareness regarding cancer diseases, exceeding the tool’s hypothetical mean.To answer the second research question, the t-value for each domain was calculated, and the results were as follows:First Domain: Food Health – There is a statistically significant difference based on gender, in favor of males.Second Domain: Environment – There is a statistically significant difference based on gender, in favor of females.Third Domain: Personal Health – There is a statistically significant difference based on gender, in favor of females.Fourth Domain: Smoking and Drugs – There is a statistically significant difference based on gender, in favor of females,These results indicate that female students demonstrated higher levels of health awareness compared to male students.